Photoelectron marginalization effect in ZnO/WO3/graphene-like composites: Study of alternating strong-low photocatalytic hydrogen production performance and mechanism - Meng, Sun; Haifeng, Zhang; Yunlong, Zhou (Journal of alloys and compounds, 2024)
ZnO/WO3/graphene-like composite photocatalysts are prepared by in-situ deposition and successfully utilized for alternating strong-low light catalytic decomposition of water to produce hydrogen. Additionally, the study details the microscopic morphology and optoelectronic properties of the ZnO/WO3/graphene-like composite. The results indicate that an internal electric field is generated between the ZnO/WO3 heterostructure and the graphene-like material. This induced electric field leads to a large amount of ordered electron transfer from ZnO/WO3 to the graphene-like material, resulting in the electron marginalization effect, which ensures the prerequisite for alternating strong-low photocatalytic splitting of water into hydrogen. When the mass fraction of the graphene-like material in the WO3/ZnO/graphene-like composite photocatalyst is 30 %, the photocatalytic hydrogen production rate reaches the maximum value of 820 times that of intrinsic ZnO. Therefore, this work provides a new perspective for alternating strong-low light catalytic water splitting to produce hydrogen. •WO3/ZnO graphene-like composite is successfully prepared.•WO3/ZnO graphene-like hydrogen rate is 1025 μmol·h−1·g−1 with strong-low light.•Mechanism of hydrogen production under strong-low light irradiation is analyzed.•Conducting photogenerated electrons in graphene like materials is analyzed.